Photocatalytic Decomposition of Methyl Red Dye by Using Nanosized Zinc Oxide Deposited on Glass Beads in Various pH and Various Atmosphere - H. R. Ebrahimi; M. Modrek (Journal of Chemistry)
Photocatalytic decomposition of methyl red (MR) as a pollutant in wastewater samples is investigated in this study. This photodegradation was investigated in water in neutral, alkaline, and acidic media under external UV light irradiation by zinc oxide nanosized catalysts on granule glass. The effect of four atmosphere types including air, nitrogen, oxygen, and argon was investigated. Finally, it was found that photodecomposition using nanosized ZnO layered on glass is a new alternative route for efficient wastewater treatment. The results showed that the titled dye is degraded by various rate under different atmosphere and pH.